THE IMPACT OF DIESEL BUS EMISSIONS ON AIR POLLUTION IN ULAANBAATAR AND ATTEMPT TO REDUCE IT - Tsetsegmaa Agvaantseren; Bayarsuren Badarch; Altantsetseg Tseveg (World Science, 2022)
The advantages of diesel engines have led it to become the only solution for heavy-duty vehicles (HDV), including city buses. Exhaust gas from diesel engines (EG) is a common environmental pollutant and carcinogenic to human health. The paper presents the results of measuring the emissions of city buses running on high sulfur fuel with and without diesel particulate filter (DPF). The study was conducted in real traffic conditions along the regular route of the city of Ulaanbaatar. The measurements were carried out using the HORIBA PEMS (Portable Emissions Measurement System) and the gravimetric method. The measured data was used to determine the actual emission levels from city buses. The actual particulate matter (PM) emissions from city buses were determined during the warm and cold seasons on a daily basis. It is found that a bus with average daily mileage of 242 km emits average of 166.155 g of PM into the atmosphere per day. This fluctuates depending on the season - 141.3 g in summer and 175.8 g in winter. The actual PM emissions of a city bus is 0.6866 g/km. The NOx concentration in the exhaust gases is 1410.94 ppm on average. As a result of 6 months of measurements, a total of 346.651 kg of soot was collected from 24 buses. Innovation: Actual on-road emissions from Ulaanbaatar buses and a cassette-type DPF system with “active” outside the bus regeneration, that can reduce conventional diesel engine PM emissions by up to 90% regardless of the sulfur content of the fuels.